Impact of the Boreal Summer Intraseasonal Oscillation on the diurnal cycle of precipitation in the island of Luzon - Chudler, Kyle, author; Rutledge, Steven, advisor; Xu, Weixin, committee member; Bell, Michael, committee member; Reising, Steven, committee member (Colorado State University. Libraries, 2019)
The Asian Summer Monsoon (ASM) is a major component of the global weather system with impacts on multiple scales. Driven by the thermal contrast between the Asian continent and the Indian and Pacific Oceans, the monsoon winds bring warm, moist air into the south Asian and maritime continents. Along with this influx of tropical air often comes copious amounts of rain, which can be both beneficial to agriculture and devastating to flood-prone regions. On a larger scale, the immense amount of latent heat released into the upper troposphere from condensation and deposition of water vapor can impact weather patterns across the globe. One striking feature in rainfall climatology of the ASM is the precipitation maxima located off the western shores of the Western Ghats, Myanmar, and the Philippines. These locations all feature elevated terrain features along their western shores. Many studies have examined why, when monsoon winds impinge upon these mountains, the precipitation preferentially falls off-shore, rather than directly over the mountains where orographic enhancement is strongest. Several theories have been proposed, including convergence of the monsoon winds with a land breeze, afternoon land-based convection which either propagates off-shore or creates a cold pool, and generation of off-shore instability through propagation of gravity waves generated from daytime heating of the boundary layer. Notably, all of these mechanisms are closely tied to the diurnal cycle. The main source of intraseasonal variability during the summer months in the ASM region is the Boreal Summer Intraseasonal Oscillation (BSISO). Characterized by a broad region of convection which propagates SW to NE from the Indian Ocean to the West Pacific, the BSISO brings alternating 2-3-week periods of inactive and active weather conditions to the monsoon region. Inactive periods are characterized by relatively clear skies, weaker winds, and localized but more intense convection over land. Active periods bring an increase in strong low-level monsoon winds and frequent, widespread precipitation and cloud cover. In this study, the impact of the BSISO on the occurrence of off-shore precipitation around the island of Luzon is examined. Satellite precipitation estimates show that off-shore precipitation occurs much more frequently during active BSISO phases. Importantly, results also show that a clear diurnal cycle still exists over land during these phases, despite increased cloud cover and reduced solar heating/instability generation. It is hypothesized that the interaction between strong low-level monsoon winds and the diurnal cycle over land is what promotes off-shore precipitation, either through the generation of wind shear (which supports off-shore propagation), or convergence between these winds and a cold pool or land breeze. The stronger low-level winds also cause greater ocean surface energy fluxes, which further promote precipitation. During inactive phases, despite the stronger diurnal cycle over land, the lack of a strong low-level wind results in an environment less conducive to off-shore rainfall.
Keywords: Luzon; precipitation; BSISO; TRMM; monsoon